Metarnal Anemia in Pregnancy and it’s Association with Low Birth weight and Development Delay in infants: A Retrospective Study - Kumar, Vijayant; Kumari, Anupam; Kumar, Anil; J.P. Narayan; Nisha, Swet; Prasad, Seema (Student’s Journal of Health Research Africa, 2024)
Background Objective: To evaluate the association of maternal anemia in pregnancy with low birth weight and developmental delay in infants within the first year of life. Methods A retrospective observational study was performed at Darbhanga Medical College and Hospital and Government Medical College, Bettiah, involving 93 mother-infant pairs from September 2015 to August 2016. Maternal hemoglobin levels were obtained from prenatal records. Infants were assessed for birth weight, gestational age, and developmental milestones utilizing conventional clinical records and follow-up documentation. Anemia was defined according to WHO criteria, and infants were classified as having normal or delayed development at 12 months based on Denver Developmental Screening Test (DDST) evidence. Results Among 93 mothers, 68 (73.1%) exhibited anemia, comprising 42 instances of moderate anemia and 7 instances of severe anemia. Of children born to anemic women, 57.4% exhibited low birth weight (<2.5 kg), in contrast to 24% in the non-anemic cohort (p < 0.01). Additionally, developmental delay was observed in 21 infants (22.6%), with 85.7% of these infants born to women experiencing moderate to severe anemia. A statistically significant correlation was identified between reduced maternal hemoglobin levels and an elevated risk of both low birth weight and developmental delay. Conclusion Maternal anemia during pregnancy markedly elevates the risk of low birth weight and developmental delays in newborns, underscoring the imperative for early screening, nutritional supplementation, and maternal health education. Mitigating maternal anemia by standard prenatal care can enhance infant outcomes and promote long-term developmental potential.